PENGARUH MODAL INTELEKTUAL, KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DAN MASA JABATAN DEWAN KOMISARIS TERHADAP KINERJA KEUANGAN PERUSAHAAN - Alif Nur Krishnamurti; Totok Dewayanto (Diponegoro Journal of Accounting, 2020)
The purpose of this study is to examine whether Intellectual Capital, Managerial Ownership, Institutional Ownership, and Board of Commissioners' Masa jabatan affect the Company's Financial Performance and company firm size and leverage as a control variable.The population in this research consists of all manufacturing companies on the Indonesia Stock Exchange in the 2015-2017 period. Sampling was done using a purposive sampling method. The total sample of this research is 210 companies.This study uses multiple regression analysis to test hypotheses. The results of this study indicate that Intellectual Capital has a positive and significant influence on the Company's Financial Performance. Meanwhile, Managerial Ownership, Institutional Ownership, and Board of Commissioners' Masa jabatan have no influence on the Company's Financial Performance